Control of Conformation and Chirality of Nonplanar π‐Conjugated Diporphyrins Using Substituents and Axial Ligands. Issue 6 (19th February 2016) - Ito, Satoru; Hiroto, Satoru; Ousaka, Naoki; Yashima, Eiji; Shinokubo, Hiroshi
Abstract: Nonplanar conformations of pyrazine‐fused Zn II diporphyrins could be controlled by the choice of the meso ‐aryl substituents and an axial ligand on the central metals. Zn II diporphyrins bearing sterically demanding meso ‐aryl groups with ortho ‐substituents led to a twisted chiral D 2 conformation, while an achiral C 2 h form was preferred in the case of aryl groups without ortho ‐substituents. Helical chirality induction on Zn II diporphyrins in the twisted conformation was achieved by controlling their handedness of the molecular twist through coordination of optically active 1‐phenethylamine. Abstract : But there′s a twist ! Conformations of nonplanar Zn II diporphyrins could be controlled by the meso ‐aryl substituents and an axial ligand on the central metals. Helical chirality induction on Zn II diporphyrins was achieved by controlling their handedness of the molecular twist through coordination of an optically active amine.